Requirement derivation of vehicle steering using mechanical four-poles. (1st November 2019) - Muenster, M.; Lehner, M.; Rixen, D.
Highlights: Mechanical four-pole coefficients are useful to identify vehicle subsystem dynamics. Four-pole coefficients are suitable to represent requirements to subsystem dynamics. Subsystem identification is feasible in practice either experimentally or virtually. Compared to other substructuring methods, fewer coefficients have to be identified. A new virtual roller test rig (MBS model) for the front axle subsystem is presented. Abstract: Vehicle design with respect to steering feel and steering vibration is challenging for many reasons. One of them is that several subsystems need to be considered simultaneously, which are developed separately by different departments or external suppliers. Therefore, the requirements, which are usually imposed on the vehicle level, i.e. the coupled system, have to be reformulated on the level of subsystems. In this work, objective requirements on the steering subsystem are derived using mechanical four-poles. For this purpose, the vehicle system is divided into steering and front axle subsystems. Basic equations are derived in order to determine the relevant four-pole coefficients and to derive requirements to the subsystems by disassembling them from given vehicle system dynamics. Both virtual and experimental methods can be used to determine the relevant four-pole coefficients of the steering and the front axle during the design and verification stages. Vehicle targets are introduced, depending on vehicle speed or excitation frequency. Then, requirements in terms of necessary, sufficient and phase-exact limit values to selected subsystem dynamics are calculated. By assembling actual and permissible dynamics of the subsystems, the performance at vehicle level becomes predictable. It is shown that target mismatch can be detected already at subsystem level during the design phase, where corrective measures are still feasible. Reversely, vehicle targets are met if the subsystems fulfill their respective requirements.